2021
DOI: 10.1002/crq.21298
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel model exploring the relationships between individual spirituality, spiritual climate, and nonviolent work behavior

Abstract: Based on Social Cognitive Theory (SCT), the present study investigated relationships between spiritual climate (environmental factor), individual spirituality (personal factor), and nonviolent work behavior. A significant association was observed between individual spirituality and nonviolent behavior. Results also concluded a significant moderation effect of spiritual climate. Transcendence, meaningful life, faith, and practicing spirituality are reported as significant predictors of nonviolent work. Two dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The link between workplace spirituality and work engagement is highlighted through trust Gupta & Mikkilineni, 2018). The scholarly gap exists since this subject is still in its infancy, even though much research has shown a statistically significant link between workplace spirituality and positive organizational outcomes Sarkar & Garg, 2021). The literature on workplace spirituality and social exchange theory highlights the potential and positive effects of workplace spirituality experienced by employees in the working place (Sibley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The link between workplace spirituality and work engagement is highlighted through trust Gupta & Mikkilineni, 2018). The scholarly gap exists since this subject is still in its infancy, even though much research has shown a statistically significant link between workplace spirituality and positive organizational outcomes Sarkar & Garg, 2021). The literature on workplace spirituality and social exchange theory highlights the potential and positive effects of workplace spirituality experienced by employees in the working place (Sibley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the spiritual climate positively affected team learning and resulted in team innovative behavior (Pandey et al, 2016(Pandey et al, , 2019. Using the social cognitive theory framework, which underscores the relevance of contexts or environment in the individual's knowledge acquisition and behavioral responses, Sarkar and Garg (2021) explain the role of individual spirituality combined with the spiritual climate of the organization in promoting non-violent workplace behavior.…”
Section: The Moderating Role Of Spiritual Climatementioning
confidence: 99%
“…The author further elaborates that this broadening process builds psychological capital for individuals. The feeling of abundance and appreciation for others fills one with hope, optimism, and resilience (Sarkar and Garg, 2021). Fredrickson also suggests that gratitude develops social capital in various ways.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the holistic construct are manifold. This holistic construct not only cultivates one's spiritual attributes (Sarkar and Garg, 2020, 2021); altogether, it affects ethical decision-making (Corner, 2009), moral reasoning (Mayton, 1992), mindful utilization of organization resources (Gandhi, 2013), social responsibilities (Narayan, 2000) and many more. However, the scope of the current paper is an attempt to conceptualize the construct as a rehumanizing response on the face of himsa /violence .…”
Section: Convergence Of the Micro And The Lifeworld In Deconstructing...mentioning
confidence: 99%